2010
DOI: 10.1158/0008-5472.can-09-4466
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-14 (MT1-MMP)–Mediated Endoglin Shedding Inhibits Tumor Angiogenesis

Abstract: Endoglin is a transforming growth factor-β coreceptor with a crucial role in angiogenesis. A soluble form of endoglin is present in the circulation, but the role of soluble endoglin (sEndoglin) is poorly understood. In addition, the endoglin shedding mechanism is not known. Therefore, we examined the role of sEndoglin in tumor angiogenesis and the mechanism by which the extracellular domain of endoglin is released from the membrane. In colorectal cancer specimens, we observed high endothelial endoglin protein … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
228
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(248 citation statements)
references
References 48 publications
17
228
0
3
Order By: Relevance
“…7). Experimental support for this hypothesis has been recently reported, demonstrating that MT1-MMP is in fact a major endoglin-shedding protease (75). This is compatible with the fact that ␤-glycan, another TGF-␤ coreceptor with a partial sequence homology to endoglin, can be shed by MT1-MMP (171).…”
Section: Role Of Other Endoglin Forms In Vascular Physiopathologysupporting
confidence: 59%
“…7). Experimental support for this hypothesis has been recently reported, demonstrating that MT1-MMP is in fact a major endoglin-shedding protease (75). This is compatible with the fact that ␤-glycan, another TGF-␤ coreceptor with a partial sequence homology to endoglin, can be shed by MT1-MMP (171).…”
Section: Role Of Other Endoglin Forms In Vascular Physiopathologysupporting
confidence: 59%
“…Hawinkels et al have shown that endoglin shedding was mediated by matrix metalloproteinase (MMP)-14 and resulted in vitro in reduced spontaneous and VEGF-induced endothelial sprouting. 20 The clinical and correlative data in our phase II study suggest that TRC105 therapy will not be effective as a single agent in the present schedule in HCC. Only one patient achieved an objective response and was progression free at four months.…”
Section: Discussionmentioning
confidence: 84%
“…Despite the fact that 129/Ola and C57BL/6 inbred endoglin haploinsufficient mice strains are available as a model of hereditary hemorrhagic telangiectasia, they do not develop atherosclerosis 48) . Inhibition of endoglin activity by antibodies has been proposed in targeted inhibition of angiogenesis during tumor development 16,49) ; however, no data about atherosclerosis and endoglin antibodies are available.…”
Section: Discussionmentioning
confidence: 99%